Integration of Talent Acceleration, Academic Pipeline, and Corporate Transformation in Building an Agility Organization Ecosystem: A Literature Review Approach - Windayanti, Windayanti; Kurnianto, Aryono (Universitas Mohammad Husni Thamrin, 2025)
Increasingly complex organizational dynamics require educational institutions and business organizations to build more adaptive, strategic, and sustainable human resource development systems. Rapid changes in the business environment due to digitalization, globalization, and organizational disruption have caused many institutions to struggle to maintain organizational sustainability. In this context, organizations are beginning to face serious challenges related to leadership gaps, talent shortages, and mismatches between the competencies of higher education graduates and industry needs. On the other hand, higher education institutions often focus on formal academic achievements without building strategic connections with the needs of modern organizations. This study aims to analyze the relationship between talent acceleration, academic pipelines, and corporate transformation in building an organizational agility ecosystem through a literature review approach. The research method uses a systematic literature review of various national and international journals discussing talent management, leadership pipelines, organizational agility, corporate transformation, and academic-industry integration. The study results show that the integration of talent development, academic acceleration based on industry needs, and organizational transformation can improve organizational adaptability, leadership sustainability, and strategic competitiveness. This study also found that universities have a strategic role as knowledge integrators in building an ecosystem transformation connected to industry needs. The contribution of this research provides a conceptual model of talent-academic-business ecosystem integration as a strategic approach in facing modern organizational disruption.